An integrated model for predicting maximum net photosynthetic rate of cocksfoot (Dactylis glomerata) leaves in silvopastoral systems - Peri, Pablo Luis (2003)
Net light-saturated photosynthetic rate ~Amax! of field grown cocksfoot ~Dactylis glomerata L.! leaves in a radiata pine ~Pinus radiata D. Don! silvopastoral system ~Canterbury, New Zealand! was measured at different times under severe shade ~85-95 mmol m–2 s–1 photosynthetic photon flux density, PPFD! and in full sunlight ~1900 mmol m–2 s–1 PPFD!. The aim was to integrate individual functions for Amax against air temperature ~2 to 37 ºC!, water status, expressed as pre-dawn leaf water potential ~clp! ~-0.01 to 2 1.6 MPa!, herbage nitrogen ~N! ~1.5 to 5.9%!, regrowth duration ~20 to 60 days! and time under shade ~1 to 180 min! into a multiplicative model. The highest Amax value obtained was 27.4 mmol CO2 m–2 s–1 in non-limiting conditions with full sunlight. This value was defined as standardised dimensionless A maxs 5 1 for comparison of factor effects. The canopy temperature of the cocksfoot sward was up to 7.4 ºC cooler than air temperature for plants under shade. Therefore, canopy temperature was used to predict Amax. The only interaction was between time under severe shade ~5% of the open PPFD! and water stress ~clp 5 2 0.4 to 2 1.3 MPa! and this was included in the model. Validation of this model indicated 78% of the variation in A max could be accounted for using these five factors by the addition of the interaction function. This model could be used to assist the prediction of pasture growth in silvopastoral systems through incorporation into a canopy photosynthesis model.